Constructing Financial Consultant Productivity through Digital Engagement in Flexible Work Arrangements: A Qualitative Study - Tri Okta Ramadhini; Muhammad Fajar Wahyudi Rahman (Master of Management, School of Business and Management, Petra Christian University, 2026)
The institutionalization of hybrid work has intensified financial consultants' reliance on digital engagement to sustain productivity under Flexible Work Arrangements (FWA). However, this process is still predominantly understood through quantitative, variable-based measures. This study aims to explore how digital engagement constructs financial consultant productivity within FWA practices in the Indonesian futures and brokerage sector. Using a descriptive qualitative case study design, data were collected through semi-structured in-depth interviews, passive participatory observation, and documentation study involving five financial consultants from Indonesian futures and brokerage companies, analyzed through reflexive thematic analysis and Miles & Huberman’s interactive model, with Job Demands-Resources (JD-R) Theory serving as a sensitizing framework. Four themes emerged: (1) digital engagement as a constructive process shaping professional identity, (2) productivity as a layered integration of market analysis and client communication, (3) digital transparency as the foundation of client trust, and (4) JD-R duality experienced differently across managerial and operational levels. These findings suggest that financial consultant productivity in hybrid work is constructed through active interaction and contextual meaning-making rather than a standardized measurable output, offering a basis for organizations to design FWA policies grounded in individual digital readiness and structured digital boundary management.